Продуктивність сортів ячменю ярого в Степу України - Сухомлин, Едуард Володимирович; Sukhomlyn, Eduard (ЦНТУ, 2025)
У магістерській роботі оцінено продуктивність, адаптивність і мінливість господарсько-цінних ознак сортів ячменю ярого в умовах Північного Степу України за вирощування після сої та соняшнику. Встановлено особливості формування густоти стеблостою залежно від попередника. Досліджено показники індивідуальної продуктивності рослин і визначено рівень урожайності та екологічну пластичність сортів. Виявлено закономірності зміни елементів структури врожаю залежно від гідротермічних умов вегетаційного періоду. Кількісно охарактеризовано реакцію сортів на дефіцит вологи та підвищені температури. Проведено економічну оцінку ефективності вирощування залежно від попередника. Уточнено вплив агроекологічних факторів на формування врожайності, що сприяє реалізації генетичного потенціалу сучасних сортів ячменю ярого. The master's thesis evaluates the productivity, adaptability, and variability of economically valuable traits of spring barley varieties under the conditions of the Northern Steppe of Ukraine when grown after soybean and sunflower. The peculiarities of stand density formation depending on the predecessor are determined. Indicators of individual plant productivity are studied, and yield levels and ecological plasticity of the varieties are assessed. Patterns in the variation of yield structure elements depending on hydrothermal conditions of the growing season are identified. The response of varieties to moisture deficit and elevated temperatures is quantitatively characterized. An economic evaluation of cultivation efficiency depending on the predecessor is carried out. The influence of agroecological factors on yield formation is уточнено, contributing to a better understanding of the realization of the genetic potential of modern spring barley varieties.
Productivity of spring barley varieties in the Steppe of Ukraine
Keywords: ячмінь ярий; сорти; spring barley; varieties